Cover Feature: β‐Zeolite‐Assisted Lignin‐First Fractionation in a Flow‐Through Reactor (ChemSusChem 18/2021). Issue 18 (27th August 2021) - Kramarenko, Alexei; Etit, Deniz; Laudadio, Gabriele; D'Angelo, Fernanda Neira
Abstract : The Cover Feature shows lignin‐first fractionation in a flow‐through reactor assisted by β‐zeolite. More information can be found in the Full Paper by A. Kramarenko et al .